2020
DOI: 10.1371/journal.pone.0233033
|View full text |Cite
|
Sign up to set email alerts
|

Field rates of Sivanto™ (flupyradifurone) and Transform® (sulfoxaflor) increase oxidative stress and induce apoptosis in honey bees (Apis mellifera L.)

Abstract: Pesticide exposures can have detrimental impacts on bee pollinators, ranging from immediate mortality to sub-lethal impacts. Flupyradifurone is the active ingredient in Sivanto™ and sulfoxaflor is the active ingredient in Transform ®. They are both relatively new insecticides developed with an intent to reduce negative effects on bees, when applied to bee-attractive crops. With the growing concern regarding pollinator health and pollinator declines, it is important to have a better understanding of any potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 56 publications
(75 reference statements)
3
33
0
5
Order By: Relevance
“…Our results revealed that daily oral intake of Sulfx for 28 consecutive days at low (79.5 mg/kg) and high dose (205 mg/kg) expert toxic influences on the male rat reproductive organs indicated by the high content of testicular MDA, GSSG, and NOx versus the reduction in GSH content in a dose‐dependent manner. These data suggested elevated LPO and reflected the occurrence of oxidative stress due to Sulfx administration in the testis, in agreement with the results reported by Chakrabarti et al 45 who reported increased oxidative stress in bees exposed to Transform® (active ingredient sulfoxaflor). Other investigations correlated oxidative stress and increased production of ROS and reactive nitrogen species (NS) to neonicotinoid toxicity 46–48 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results revealed that daily oral intake of Sulfx for 28 consecutive days at low (79.5 mg/kg) and high dose (205 mg/kg) expert toxic influences on the male rat reproductive organs indicated by the high content of testicular MDA, GSSG, and NOx versus the reduction in GSH content in a dose‐dependent manner. These data suggested elevated LPO and reflected the occurrence of oxidative stress due to Sulfx administration in the testis, in agreement with the results reported by Chakrabarti et al 45 who reported increased oxidative stress in bees exposed to Transform® (active ingredient sulfoxaflor). Other investigations correlated oxidative stress and increased production of ROS and reactive nitrogen species (NS) to neonicotinoid toxicity 46–48 .…”
Section: Discussionsupporting
confidence: 92%
“…Caspases are crucial mediators of apoptosis, among them caspase‐3 is a frequently activated protease that catalyzes the cleavage of several structural and regulatory proteins essential for cell survival and maintenance. Its activation increases under pesticide stress in all organisms 45 . An increase in the occurrence of germ cell apoptosis is commonly reported following toxicant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Hesselbach et al (2020) recently showed that chronic exposure to FPF can lead to the premature onset of foraging in A. mellifera. Additionally, exposure to field rates of Sivanto TM (FPF) and Transform â (SULF) has also recently been shown to increase oxidative stress and induce apoptosis in A. mellifera (Chakrabarti et al, 2020). Studies have yet to investigate interactions between sublethal doses of these two novel pesticides and viral pathogens that affect honey bee health.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, six products were also recently released based on the active ingredient sulfoxaflor, a new sulfoximine class insecticide, and three more containing lambda-cyhalothrin (pyrethroid) and sulfoxaflor, totaling nine products using that active ingredient (Agrofit, 2019). Interestingly, sulfoxaflor usage has been related to several sublethal impacts and increase in bee mortality worldwide (Siviter, Brown & Leadbeater, 2018;Chakrabarti et al, 2020;Azpiazu et al, 2021). After many member states of the European Union have banned the use of neonicotinoids insecticides such as imidacloprid, clothianidin, and thiamethoxam outside greenhouse structures, sulfoxaflor arrived on the market as a differentiated neonicotinoid, because it acts on the insect nicotinic acetylcholine receptor (nAChR) in a distinct manner relative to neonicotinoids (Millot et al, 2017).…”
Section: Brazilian Legislation and Its Relation With The Increased Release Of Pesticides And Bee Mortalitymentioning
confidence: 99%